Rancang Bangun Lampu Otomatis Menggunakan Sensor PIR dan LCD Display Berbasis Tinkercad - Suratin; Fadhilah, Cut (Jurnal Elektronika dan Teknologi Informasi, 2025)
Manual control of lighting in households often leads to energy wastage, as people may forget to switch off the lights after leaving a room, resulting in unnecessary electricity consumption. To address this challenge, an automation system has been designed to enhance energy efficiency by regulating lighting based on human presence and the surrounding light levels. This system utilizes two sensors: a Passive Infrared (PIR) sensor, which detects human motion within its detection range, and a Light Dependent Resistor (LDR) sensor, which measures the intensity of ambient light. The PIR sensor operates effectively for about ± 2 minutes after activation, while the LDR sensor continuously monitors light levels and automatically controls the lighting, turning it on or off based on preset conditions. This system ensures that lights are only active when necessary, thus contributing to significant energy savings.